Multi-perspective influence mechanism analysis and multi-scenario prediction of China's carbon emissions. (23rd January 2020) - Yi, Tao; Qiu, Mohan; Zheng, Hao; Liu, Jinpeng
Due to the mandatory push to meet the carbon emission reduction commitments proposed in the Paris Agreement, an analysis of the peak carbon emission production times in China is required. This paper focuses on the peak production times of the total carbon emissions (TCEs) and carbon emissions intensity (CEI) in China. According to the development of China's carbon emissions and related targets in the 13th Five-Year Plan, the peak production times of TCE and CEI in different scenarios are predicted based on an influence mechanism analysis of China's carbon emissions from the perspectives of energy, economy, and society. Considering the development characteristics of China at this stage, this paper introduces several new indicators including the full-time equivalent of research and development (R&D) personnel and the investment in environmental pollution control. Based on the results of the study, several policy recommendations are put forward to fulfil China's carbon emission reduction commitments.